Risk Mitigation Strategy for Coal Transshipment - Noufal Zhafira; Triwulandari Satitidjati Dewayana; Dedy Sugiarto (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2023)
Coal transshipment necessitates efficient and prompt execution, devoid of any delays or work-related accidents. Numerous events during the transshipment process have the potential to disrupt operations and pose substantial risks. This research aims to examine the risks associated with coal transshipment by leveraging ISO 31000:2018 as the risk analysis framework. Additionally, it seeks to prioritize risk mitigation strategies employing the Techniques for Other Preferences by Similarity to Ideal Solutions (TOPSIS) methodology. Data collection for this study involved surveys and expert discussions to comprehensively analyze all risks by ISO 31000:2018 guidelines. The findings were then visualized through the use of a fishbone diagram, which facilitated the identification and understanding of the generated risks. The analysis revealed several threats that could impact the coal transshipment process. These major threats include natural disasters, equipment failures, shipping accidents, health risks for workers, fire hazards, operational delays, inefficient loading and unloading processes, and transportation accidents. The proposed mitigation strategies such as designing SOPs, developing emergency response plans, implementing safety measures, providing training, conducting risk assessments, and ensuring equipment maintenance, are academically supported and practical in their application. However, challenges such as financial constraints, resistance to change, and the dynamic nature of the process need to be overcome for effective implementation. Organizations can enhance safety and operational efficiency in coal transshipment by carefully managing resources, engaging stakeholders, and continuously evaluating and improving strategies. Overall, the proposed strategies offer a feasible and proactive means to mitigate threats and promote a safer and more efficient transshipment process.